Cultural differences in perceiving co-present phone use as phubbing: Evidence from six countries - Christiane M. Büttner; Elianne A. Albath; Rainer Greifeneder (Social Influence)
Phubbing is feeling excluded and ignored by someone using a phone during a face-to-face interaction. Phubbing has mostly been investigated in Western samples. However, culture likely shapes whether co-present phone use is perceived as phubbing (phubbing perception). 588 participants from collectivist (India, Kenya, Venezuela) and individualist countries (Austria, Belgium, UK) rated 25 vignettes (k = 14,700) describing co-present phone use concerning the perception of phubbing and attribution of others’ behavior. Descriptively, collectivist participants are more likely to feel phubbed (p = .065) and they significantly attribute others’ behavior more internally. Attribution mediates the influence of culture on phubbing perception. Our findings highlight the importance of investigating phubbing as a subjectively construed experience that is shaped by culture.